Why be afraid of math? : and other intellectual adventures - Lee, Queena N. (Manila : Bookmark, 1991)
A collection of essays that encourages readers to appreciate mathematics by exploring its ideas, logic, and role in intellectual inquiry. The author discusses common fears surrounding mathematics and presents engaging reflections designed to inspire curiosity and critical thinking.
Keywords: Mathematics -- Popular works; Reasoning -- Popular works